THE EFFECT OF SLOW STROKE BACK MASSAGE (SSBM) TO THE CHANGE OF THE PAIN INTENSITY IN PATIENTS WITH ACUTE LOW BACK PAIN (LBP) - Gayu Saritri Husnaa; Nur Setiawati Dewi (Jurnal Keperawatan Diponegoro, 2012)
About 80% of population has experienced in low back pain (LBP). One of non-pharmacological intervention to overcome LBP is using Slow Stroke Back Massage (SSBM). The mechanism of SSBM in reducing the intensity of pain is using the principle of gate control theory. This study aims to determine the effect of SSBM to the change of pain intensity in patients with acute LBP. Pre-experimental study was conducted one group pre and post test without comparison group. The sample of study is 32 housewives experienced in acute LBP taken by purposively sampling. The technique of data collection is by measuring the pain intensity before and after SSBM using VAS. Based on the statistical analysis obtained the average of pain intensity before SSBM 4.913 ± 2.2441 with pain intensity range 0.6-8.2, median 4.950. The average of pain intensity after SSBM is 2.491 ± 1.6308 with pain intensity range 0-5.4, median 2.450. While the test paired t-test showed that p=0.0001 (p <0.05) which means there is a change in pain intensity before and after the SSBM. Therefore we can conclude that there is an effect of SSBM to the change of pain intensity in patients with acute LBP. We can conclude that nurse as a care provider can do SSBM for the non-pharmacological therapy of acute LBP